The History of the Contempt Power - Ronald Goldfarb (Washington University Law Quarterly, 1961)
The American ideology is one based upon recognition of the rights and liberties of the individual. This concept was ensured by the architects of our government when they created this republic, one in which all men are, at least philosophically, sovereign, while government is but the vehicle of their sovereignty. The manifestation of this dream was encouraged by bitter memories of monarchial experience-the hope for individual liberation. How can it then be that man can be contumacious to a sovereign which is, theoretically at least, the ultimate extension of himself; or inversely, should government, created by, of, and for man be allowed to punish the exercise of the will of its constituent self? And if so, is the summary contempt procedure, by which the contemnor is brought before and tried by the offended party, without jury, counsel, defense, and ordinary appeal, either right or reasonable? Is this scheme of governmental power consistent with our constitutional principles of jury trial, self-incrimination, non-excessive punishments, free press and speech, double jeopardy, fair trial?
Keywords: Contempt